2022
DOI: 10.1371/journal.pgph.0000934
|View full text |Cite
|
Sign up to set email alerts
|

Using a health belief model to assess COVID-19 vaccine intention and hesitancy in Jakarta, Indonesia

Abstract: Since January 2021, Indonesia has administered a nationwide COVID-19 vaccination. This study examined vaccine intention and identified reasons for vaccine hesitancy in the capital city of Jakarta. This is a cross-sectional online survey using the Health Belief Model (HBM) to assess vaccine intent predictors and describe reasons for hesitancy among Jakarta residents. Among 11,611 respondents, 92.99% (10.797) would like to get vaccinated. This study indicated that all HBM constructs predict vaccine intention (P&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…This finding correlates to a study in Italy, which found that PLHIV believed that their condition was associated with a higher risk of developing complications of COVID-19 infection ( p = 0.013) [ 28 ]. A previous study in Indonesia using the health belief model on the general population also demonstrated a similar association between vaccination willingness and the perceived benefits of COVID-19 vaccination [ 29 ].…”
Section: Discussionmentioning
confidence: 55%
“…This finding correlates to a study in Italy, which found that PLHIV believed that their condition was associated with a higher risk of developing complications of COVID-19 infection ( p = 0.013) [ 28 ]. A previous study in Indonesia using the health belief model on the general population also demonstrated a similar association between vaccination willingness and the perceived benefits of COVID-19 vaccination [ 29 ].…”
Section: Discussionmentioning
confidence: 55%
“…This result confirms that vaccine refusal or delay results from an imbalance between the perception of the vaccine-related risk and benefits associated with vaccination: individuals who weigh the risks related to vaccination higher than its benefits will tend to refuse or delay some or all vaccines [ 33 , 45 , 46 ]. The health belief model supports this finding by highlighting that perceptions of vaccine efficacy and concerns about vaccine-related side effects may hinder subjects from getting vaccinated [ 47 ]. Furthermore, in this study, a higher percentage of unvaccinated individuals believed that getting vaccinated was risky due to negative experiences reported by their relatives, friends, and acquaintances.…”
Section: Discussionmentioning
confidence: 92%
“…Contrastingly, other scholars suggested that fear of risk-prevention techniques (e.g., breast cancer screening) led to perceived barriers to adopting the early detection procedure (Emami et al, 2021; Talbert, 2008). By the same token, Hidayana et al (2022) also reported that fear of the needle led to perceived barriers to adopting the COVID-19 vaccines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, as negative health beliefs may enhance one's threat perception, the latter may also generate fear (H. Lu et al, 2020;Nabi & Prestin, 2016). Yet, negative emotions such as fear about a risk-prevention technique could also elicit negative risk perceptions (Emami et al, 2021;Hidayana et al, 2022;Talbert, 2008).…”
Section: Main Findingsmentioning
confidence: 99%